Near-Infrared II Gold Nanocluster Assemblies with Improved Luminescence and Biofate for In Vivo Ratiometric Imaging of H2S - Li, Shihua; Ma, Qiuping; Wang, Chenlu; Yang, Kaidong; Hong, Zhongzhu; Chen, Qiushui; Song, Jibin; Song, Xiaorong; Yang, Huanghao (Analytical chemistry (Washington), 2022)
Ultrasmall gold nanoclusters (AuNCs) are emerging as promising luminescent nanoprobes for bioimaging due to their fantastic photoluminescence (PL) and renal-clearable ability. However, it remains a great challenge to design them for in vivo sensitive molecular imaging in desired tissues. Herein, we have developed a strategy to tailor the PL and biofate of near-infrared II (NIR-II)-emitting AuNCs via ligand anchoring for improved bioimaging. By optimizing the ligand types in AuNCs and using Er3+-doped lanthanide (Ln) nanoparticles as models, core–satellite Ln@AuNCs assemblies were rationally constructed, which enabled 2.5-fold PL enhancement of AuNCs at 1100 nm and prolonged blood circulation compared to AuNCs. Significantly, Ln@AuNCs with dual intense NIR-II PL (from AuNCs and Er3+) can effectively accumulate in the liver for ratiometric NIR-II imaging of H2S, facilitated by H2S-mediated selective PL quenching of AuNCs. We have then demonstrated the real-time imaging evaluation of liver delivery efficacy and dynamics of two H2S prodrugs. This shows a paradigm to visualize liver H2S delivery and its prodrug screening in vivo. Note that Ln@AuNCs are body-clearable via the hepatobiliary excretion pathway, thus reducing potential long-term toxicity. Such findings may propel the engineering of AuNC nanoprobes for advancing in vivo bioimaging analysis.